Quality attributes of selected leafy vegetables - Maya Mathew (Department of Home Science, College of Horticulture, 2000)
The study entitled 'Quality attributes of selected leafy vegetables' was undertaken to estimate the nutrient composition, anti-nutritional factors and organoleptic qualities of eight leafy vegetables, along with the control variety, Amaranthus tricolor L. available and maintained in the Department of Olericulture, College of Horticulture, Vellanikkara. All the above attributes were evaluated during summer and rainy seasons. The leaves were analysed for moisture, protein, fat, fibre, starch, soluble carbohydrates, calcium, phosphorus, iron, beta-carotene and vitamin C. The results revealed that among the different constituents, the mean protein content of the . .control variety. was found to be significantly higher than the other leafy vegetables. All the leafy vegetables were found to be rich in iron, beta-carotene and vitamin C. The mean fibre, soluble carbohydrate and vitamin C contents were highest in centella, whereas bengalkeera had the highest mean value for starch and calcium. The highest phosphorus, iron and beta-carotene contents were in kangkong leaves. Except the beta-carotene content during summer season, all the other constituents of the different leafy vegetables varied significantly during summer and rainy seasons. However, significant increase in the calcium, phosphorus, iron and vitamin C contents were observed during rainy season. The average nutritive values computed on the basis of the nutrient content of the leafy vegetables, revealed that kangkong had the highest nutritive value among the leafy vegetables selected for the study. The average nutritive value of the leaves was also found to be higher during rainy season. The anti-nutritional factors namely, oxalates and nitrates in the leaves were also analysed during summer and rainy seasons. The results revealed that bengal keera and Amaranthus tricolor L. had the highest oxalate and nitrate contents respectively than the other leafy vegetables. Variation in both the anti-nutritional